2013
DOI: 10.1155/2013/539348
|View full text |Cite
|
Sign up to set email alerts
|

Vitronectin Absorbed on Nanoparticles Mediate Cell Viability/Proliferation and Uptake by 3T3 Swiss Albino Mouse Fibroblasts: In Vitro Study

Abstract: We study the interaction of 3T3 Swiss albino mouse fibroblasts with polymeric nanoparticles (NPs) and investigate cellular behaviour in terms of viability/cytotoxicity, cell cycle, NPs uptake, MAP kinase (ERK1/2), and focal adhesion kinase (FAK) activation. After incubation of NPs with cell culture media, western blot analysis showed that Vitronectin is retained by NPs, while Fibronectin is not detected. From cytotoxicity studies (MTT and BrdU methods) an LD50 of about 1.5 mg/mL results for NPs. However, NPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Vinculin is also known to inhibit FAK interactions and phosphorylation and it has been demonstrated previously that vinculin‐depleted cells had increased motility, proliferation, and supressed apoptosis . Increased cell proliferation is also linked with increased phosphorylation of FAK together with cell cycle progression and increased motility . Results herein show that nano‐TiO 2 modified the expression of vinculin in a size dependent manner, that is, decreased expression in Ti5‐treated cells and increased expression in Ti40‐treated cells.…”
Section: Discussionsupporting
confidence: 66%
“…Vinculin is also known to inhibit FAK interactions and phosphorylation and it has been demonstrated previously that vinculin‐depleted cells had increased motility, proliferation, and supressed apoptosis . Increased cell proliferation is also linked with increased phosphorylation of FAK together with cell cycle progression and increased motility . Results herein show that nano‐TiO 2 modified the expression of vinculin in a size dependent manner, that is, decreased expression in Ti5‐treated cells and increased expression in Ti40‐treated cells.…”
Section: Discussionsupporting
confidence: 66%
“…Rosso et al (2013) have shown that plasma vitronectin bound to certain nanomaterials (maleic anhydride/alkyl vinyl ethers-based NPs) triggers activation of the vitronectin-integrin receptor. This activation leads to increased phosphorylation of ERK1/2 and FAK kinases and increased proliferation and cell cycle progression.…”
Section: 4 Interaction Of Nanomaterials With Proteins and Impact Onmentioning
confidence: 99%
“…This activation leads to increased phosphorylation of ERK1/2 and FAK kinases and increased proliferation and cell cycle progression. In addition, the authors found that the NPs were internalized by cells through a direct interaction between the NPs and the vitronectin-integrin receptor (Rosso et al, 2013). …”
Section: 4 Interaction Of Nanomaterials With Proteins and Impact Onmentioning
confidence: 99%
“…The serum protein corona is very complex, consisting of various of proteins including apolipoproteins, adhesion mediators, signaling and transport proteins, complement components, and coagulation factors. 34 Therefore, the western blot method was used to investigate the adsorption of the above adhesion mediators (Fn, Vn, Ln and Fgn) from 10% FBS solution ( Fig. 33 It was known that the adhesion mediators such as Fn, Vn, Ln and Fgn can interact with receptors of cells through their RGD domains, which in turn modulate the cellular uptake.…”
Section: Protein Adsorption On Ma-aunpsmentioning
confidence: 99%